Cardiac function in Vietnamese patients with different dengue severity grades - Yacoub, S; Griffiths, A; Hong Chau, T; Simmons, C; Wills, B; Hien, T; Henein, M; Farrar, J (2012)
Objective: Dengue continues to cause significant global morbidity and mortality. Severe disease is characterized by cardiovascular compromise from capillary leakage. Cardiac involvement in dengue has also been reported but has not been adequately studied. Setting: Hospital for Tropical Diseases, Ho Chi Minh City, Vietnam. Subjects and Design: Seventy-nine patients aged 8-6 yrs with different dengue severity grades were studied using echocardiography including tissue Doppler imaging. The patients were split into severity grades: dengue, dengue with warning signs, and severe dengue. Changes in cardiac functional parameters and hemodynamic indices were monitored over the hospital stay. Intervention: None. Measurements and Main Results; Patients with severe dengue had worse cardiac function compared with dengue in the form of left ventricular systolic dysfunction with increased left myocardial performance index (0.58 [0.26-0.80] vs. 0.38 [0.22-0.70], p = .006). Septal myocardial systolic velocities were reduced (6.4 [4.8-10] vs. 8.1 [6-13] cm/s, p = .01) as well as right ventricular systolic (11.4 [7.5-17] vs. 13.5 [10-17] cm/s, p = .016) and diastolic velocities (13 [8-23] vs. 17 [12-25] cm/s, p = .0026). In the severe group, these parameters improved from hospital admission to discharge; septal myocardial systolic velocities to 8.8 (7-11) cm/s (p = .002), right ventricular myocardial systolic velocities to 15.0 (11.8-23) cm/s, (p = .003), and diastolic velocity to 21 (11-25) cm/s (p = .002). Patients with cardiac impairment were more likely to have significant pleural effusions. Conclusions: Patients with severe dengue have evidence of systolic and diastolic cardiac impairment with septal and right ventricular wall being predominantly affected. Copyright © 2012 by the Society of Critical Care Medicine and Lippincott Williams and Wilkins.